"H"‐like Organic Nanowire Heterojunctions Constructed from Cooperative Molecular Assembly for Photonic Applications. Issue 11 (14th July 2015) - Yao, Wei; Han, Guangchao; Huang, Fu; Chu, Manman; Peng, Qian; Hu, Fengqin; Yi, Yuanping; Jiang, Hua; Yao, Jiannian; Zhao, Yong Sheng
Abstract : "H "‐like organic nanowire heterojunctions with two parallel 2‐acetyl‐6‐dimethylamino‐naphthalene wires vertically bridged by one 2, 4, 5‐triphenylimidazole wire are prepared via cooperative molecular assembly in liquid phase. The exciton conversion at the junction interfaces is beneficial for the design of multichannel light‐controlled photoswitches. The results provide better understanding of molecular assembly toward specific structures and open up new prospects for the creation of novel photonic materials.